Teaching aircraft design with flyable prototype - Muhamad, Sallehuddin (2012)
Aircraft design, a final year subject, integrates knowledge in aerodynamics, structure, stability and control, propulsion system and performance of an aircraft. In many universities, students will produce a conceptual design based on a Request for Proposal document. As a university that adopts Outcome-Based Education (OBE) concept, students in Universiti Teknologi Malaysia (UTM) are not only expected to apply knowledge to solve design problems but also skillful and able to work as a team. Using Problem-Based Learning technique, students taking the Aircraft Design subject are taught design technique and skills to build a flyable prototype. The challenges faced by instructor are ensuring the originality of the design and prototype is completed within budget and dateline.